Environmental toxicology and chemistry in Latin America - Carriquiriborde, Pedro (2012)
Environmental toxicology and chemistry in Latin America is a relatively young discipline. Whereas the first international publications in the United States, for example, can be tracked to the 1920s and 1930s [1–4], in Latin America the earliest international publications appeared in the 1970s [5–14] (Fig. 1). Two accelerations can be observed in the growth rate of scientific production in Latin America: the first in the 1990s, involving most of the region, followed by another in 2000– 2005, particularly in Brazil and Argentina. Figure 1 shows that more than 90% of Latin America’s total scientific production published in international journals is concentrated in only five countries: Brazil, Mexico, Argentina, Chile, and Colombia. This indicates that concern and development of scientific capabilities to face environmental issues remain a challenge for many Latin American countries. Strengthening scientific collaboration across Latin American countries could contribute to a more even development of the discipline in the entire region.